Macro and Microeconomic Variables on Stock Return in The Property Sector In 2018-2022 - Yuwono, Wisnu; Andrianus, Lian; Laulita, Nasar Buntu (Journal of Economic, Management, Accounting and Technology (JEMATech), 2024)
The purpose of the study, is getting information about investment to the investor based on micro and macro economic indicator. The variabel of micro and macro economic have a fluctuation indicated to Stock Return variabel. In this study, Stock Return is a dependent variable, Return On Asset (ROA), Debt to Equity Ratio (DER), Current Ratio (CR), Inflation, and Interest Rate is independent variable. The sample is using 23 of property company in 2018-2022 years. Variable data of macro economic is collect from website on www.bi.go.id, www.bps.co.id and data variable of micro economic is collect from company financial statement. The methods of this study is using analisis liner berganda. The result of this study is using the common effect model, because is the best model in this study. The result of Uji F is show ROA, DER, CR, Inflation and Interest Rate is not simultaneous significant to the Stock Return. The Result of Uji T is show the effect of ROA, DER and CR is not significant to the Stock Return, otherwise the Inflation and Interest Rate is significant to the Stock Return.